Learning from nature : experimental observation and measurement of mimosa pudica - Fang, Hui Ying (Nanyang Technological University, 2021)
Mimosa Pudica is sensitive to stimuli of mechanical, electrical, heat, light, and wind. The plant displays rapid leaf movement in response to stimulations. The leaves fold inward and drop downwards and then re-open several minutes later. There are quite a few interesting points we can study from Mimosa pudica. In fact, many detailed researches have been conducted. There are studies on the effect of different types of stimulations on Mimosa Pudica. There are studies on the learning paradigms between Mimosa pudica and animals from their movements towards external stimuli. There are also studies on fatigue life in terms of closing and re-open time and speed. In this study, it was focused on the study of movement features, specifically the droop angle, and fatigue life in relation to different petiole length sample of Mimosa pudica. For the study, test specimens were wild Mimosa pudica located in multiple areas in Singapore. Each unique petiole represents one test sample which may contain multiple leaflets or sub petiole in some cases. Experiment data and readings such as droop angle, response time upon stimuli and time span for it to recover in one cycle are recorded down and tabulated. The results revealed that petiole length and other factors have limited explicit influence on the movement behaviors of Mimosa pudica. For all test samples, as cycles repeat until near fatigue limit, they had common behaviors that droop angle were found smaller and smaller, and both response time recovery time became longer.